(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Personal identification is the primary aim of anyforensic investigations. Foot impressions, either 2D or 3D are used for person identification. Foot impression found on soft surfaces is three dimension in nature (3D), also namedfoot outline which shows the boundaries of the foot left by the offenders on soft surfaces. It is a fact that 3D impressions can also be used to determine stature, body weight and gender. In the developing countries, people are still walking barefooted. Earlier foot impression studies were conducted on mixed population and currently researchers are insisting the importance of ethnicity consideration.Malaysian Indians are an important ethnic group living in Malaysia, with minor sub-ethnicgroups such as Malayali, Telugu, Sikh, Tamil, and others. Hence this study intends to examine the relationship between stature and 3D foot lengths among Malaysian Telugus, mostly living in peninsular Malaysia. The stature and foot outlines (3D) were collected from consented Telugu 140 subjects, comprising 73 males and 67 females, age ranging from 18 to 60 years old. The data obtained were analysed statistically using SPSS software version 21.0. There exists a strong positive correlation between stature and 3D foot impression lengths and the correlation coefficient (R) values are found to be higher in unknown gender/pooled samplefollowed by males and females. This study developed regression formulae to determine stature from foot outline (3D) lengths among Malaysian Telugus for crime scene investigation. The equations are population specific and should not be used for any other populations.